PENCEGAHAN PENODAAN AGAMA (Kajian atas UU NO.1 TAHUN 1965) - Hanna, Siti (IAIN Pekalongan, 2010)
Government has right to issue rules that is viewed benefit its citizens in the future. Moreover, it is its main responsibility to guarantee benefit. Indonesia, as a nation that has various citizens from ethnic, tradition, language, religion, and belief, certainly need regulations that are able to maintain harmony relation among them, so that the difference is not a disunion factor. One of them is the issue of the Bill No. 1/PNPS/1965 that can be said as a real proof that Indonesia maintains the harmony of religious life.